A review of localised Māori community responses to Covid-19 lockdowns in Aotearoa New Zealand. (March 2023) - Cassim, Shemana; Keelan, Teorongonui Josie
Aotearoa New Zealand has been commended for the overarching effectiveness of its Covid-19 response. Yet, the lockdowns challenged the health of whānau Māori (Māori families) alongside their social, cultural and financial well-being. However, Māori have repeatedly demonstrated innovative means of resilience throughout the pandemic. This review aimed to document the local grassroots, community-level responses to Covid-19 lockdowns by Māori. Three sources for searching for evidence were used: academic, websites and media, and Māori community networks. A total of 18 records were reviewed. Four of these records comprised published academic literature, 13 comprised news, online and media articles, and one was a situation report. Findings were grouped into three categories: distributive networks, well-being and resource support. The findings of this review provide an exemplar for the strength of Māori leadership and agency, alongside value-driven holistic approaches to health and well-being that could positively impact the health of all.